A study of biology and parasitoid complex (Hymenoptera: Eulophidae) of leaf miners weevil Orchestes betuleti (Panzer, 1795) (Coleoptera: Curculionidae) in Ulyanovsk region - I.S. Strakhova; A.A.Zotov (Кавказский энтомологический бюллетень, 2010)
In this work we present a research of biology of the leaf miner weevil Orchestes betuleti (Panzer, 1795) (= Rhynchaenus rufus (Schrank, 1781)) (Coleoptera: Curculionidae) in Ulyanovsk region. Short diagnosis of the preimaginal stages of weevil is given. Parasitoid complex of weevil Orchestes betuleti on Ulmus pumila and U. laevis was investigated for the first time: Minotetrastichus frontalis (Nees, 1834), Aprostocetus sp., Closterocerus trifasciatus Westwood, 1833, Pediobius saulius (Walker, 1839) and Chrysocharis submutica Graham, 1963 (Hymenoptera: Eulophidae). M. frontalis is dominant ectoparasitoid species which infests more than 42% of larvae and pupae and the effective natural agent to suppress phytophagous population.